Technical Functional Properties of Crude Water Soluble Polysaccharide From Durian Seed (Durio zibethinus Murr.) - ., Herlina; Lindriati, Triana; Novijanto, Noer; Anggraini, Ayu (UNEJ e-Proceeding, 2014)
Durian seeds can be utilized as a producer of Water Soluble Polysaccharide (WSP) that can be applied to food products because crude extract of WSP is hydrocolloid. WSP interacts with other components, directly and indirectly affect processing applications, food quality, and acceptance.Water binding, solubility, viscosity and surface activity are important properties, determining usefulness and final product quality in a food system. The absence of extraction conditions that support so that the need for improved methods to variations in temperature and long extraction. This study aim to determine the effect of temperature and long extraction that produces the highest yield value and to determine the functional properties of the WSP.Â The results of this study are the highest yield values in the 50 oC temperature extraction ang long extraction 2 hours amounted to 2,26%, solubility in water of 51,61%; lightness 34,14; water holding capacity (WHC) 2339,35%;Â oil holding capacity (OHC) 425,36%; emulsion power 55,77m2/g; emulsion stability 585,50 minutes, foaming power 157,39 ml/g; foaming stability 25,43%. Long extraction increase the value of WHC and OHC but discrease the value of water solubility, foaming power and lightness. Keywords: durian seed, water soluble polysaccharide, extraction, technical functional properties.